THU0536 Childhood onset of behÇet disease (BD) symptoms in an adult cohort of BD patients. (15th June 2017) - Paisal, V; Al-Abadi, E; Protheroe, S; Carruthers, D; Situnayake, D; Powell, S; Mitton, D; Southwood, T
Abstract : Background: Behçet Disease (BD) is rarely reported in children. It a systemic inflammatory condition characterised by autoinflammatory and vasculitic clinical features including recurrent oral aphthosis, genital ulceration, skin, eye, neurological and vascular inflammation, which is most commonly diagnosed between 20–40 years of age. It is unclear how many adult patients with BD have the onset of symptoms during childhood. Objectives: The aim of our study was to investigate the age of symptom onset in a large cohort of adult patients with BD. Methods: Since 2012, the Behçet Syndrome National Centre of Excellence, Birmingham and Midland Eye Centre, has used a multidisciplinary approach aiming to shorten time to diagnosis of BD, reduce blindness and morbidity, improve knowledge and ensure equity in access to biological therapies. Patient demographic and disease information, including patient recalled age at symptom onset, symptom sequence, documented clinical signs, treatment and outcome data are maintained in a secure web-based clinical data archive. For this study, the database was interrogated to determine patient age at recalled onset of the first BD symptoms, the sequence in which symptoms appeared and whether the ISG classification criteria for the diagnosis of BD were fulfilled before the age of 16 years. Results: To June 2016, 478 patients aged between 11–68 years had data recorded in the BD database. 60 patients (12.7%, 49 females) who fulfilled International Study Group criteria for the diagnosis of BD, reported that the onset of their first symptoms was before the age of 16 years (range 2–15 years). All 60 patients reported recurrent oral ulceration and 55 reported genital ulceration but with a reported time interval between the onset of these 2 features of 0–44 years. Of the 60 patients, 26 patients reported sufficient symptoms to have fulfilled ISG criteria before their 16th birthday, including the coincident onset of recurrent oral and genital ulceration in 15/26 patients. Eye disease was only reported in 1 patient and a positive family history of BD in 5/26 patients. 11/26 patients reported a delay between the onset of oral and genital ulcers of a mean of 5.45 years (range 1–11 years). Conclusions: Many adults with BD recall the onset of their first symptoms before their 16th birthday, usually with recurrent oral and genital ulceration. We speculate that greater awareness of BD in childhood may reduce the delay in diagnosis of this chronic condition. Disclosure of Interest: None declared